Utilization of [Bmim]BF4-MAE on enhancement of γ-oryzanol extraction from rice bran and its tyrosinase inhibitory activity (Brazilian Journal of Pharmaceutical Sciences, 2020)
This study investigated the effect of ionic liquid (IL)-microwave assisted extraction (MAE) on γ-oryzanol extraction from rice bran (Oryza sativa L.). The conditions included the concentration of IL, liquid (IL)/ solid (sample) ratio, extraction time, and microwave power. The use of 1-butyl-3-methylimidazolium ([Bmim]BF4) as a selected solvent in IL-MAE method was developed for extraction of γ-oryzanol from rice bran. The Box-Behnken design on four factors with response surface methodology (RSM) was used to optimize the experimental conditions. The optimum conditions for the MAE were a [Bmim]BF4 concentration of 0.7 M, liquid/solid ratio of 15 mL/g, extraction time of 10 minutes, and 30% microwave power with a γ-oryzanol value of 0.41 mg/g. The experimental values agreed with those predicted by the RSM models. A microplate reader method was used to determine the IC50 value in tyrosinase inhibitory activity of the extract. An IC50 value of the extract obtained from IL-MAE was 1240 µg/mL. This study suggests that IL-MAE is suitable for the extraction of γ-oryzanol from rice bran and that under the optimum conditions the extract has low activity as a tyrosinase inhibitor.